Dari Kota Tradisional Menjadi Kota Kolonial: Dinamika Perkembangan Kota Singkawang pada Awal Abad XX - Firmansyah, Andang; Mirzachaerulsyah, Edwin; Prabowo, Mohammad Rikaz (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This study aims to examine the dynamics of Singkawang City's development in the 20th century. This development was marked by the growth of various urban infrastructures that supported the economy and population mobility, causing the city to transform from a traditional city into a colonial city. This study employs a qualitative method using literature review, drawing on written sources such as books, journal articles, and various studies previously conducted that are related to Singkawang City. The findings of this study indicate that the transformation of Singkawang City from a traditional city to a colonial city was marked by the Dutch beginning to build infrastructure, establish administrative governance, and implement policies within the city. The growth of Catholic missionaries during this period also brought changes to Singkawang City, particularly in the fields of education and health, as they helped build various facilities such as Catholic churches, schools, and hospitals. The transition from a traditional city to a colonial one did not erase the multicultural identity of Singkawang's society, as the changes occurred primarily in infrastructure and government administration.